The use of phone in adolescence and its interference in interpersonal relations at this phase (Research, Society and Development, 2022)
Technological evolution followed human development and its needs, transforming the habits and behaviors of individuals in the face of society.  The invasion of technology in people's lives can be more noticeable when it comes to adolescence, because at this stage the individual is meeting with himself and with the environment where he lives.  In this context, in addition to physical transformations, psychological changes also occur and technological interference in this period can lead to adolescents' withdrawal from real life, changing their way of thinking, acting and organizing themselves in front of the environment.  This study aimed to explore and describe aspects related to cell phone use in adolescence, in interpersonal relationships.  The research was developed through a bibliographic survey in the main resources that deal with the subject such as: articles and books.  It can be concluded that technology has negative and positive consequences.  It helps parents, school and friends in communication, organizing tasks and locating teenagers, but at the same time its excessive use can damage the teenager's relationship with people and, in addition, lead to depression, psychological problems and social isolation.  Given this reality, it is necessary to adopt measures to minimize such impacts.